Сценарний підхід до оцінки ризиків інформаційної безпеки на основі теорії нечіткої логіки - Діденко, Є. С. (ХНУРЕ, 2023)
This work is devoted to the study of the scenario approach to the assessment of information security risks based on the theory of fuzzy logic. The quantity and complexity of cyber threats rises at an equivalent rate to the ever-increasing reliance on information technology systems. Creating scenarios based on prospective risks is a key component of a scenario-based approach to risk assessment. Organizations can use fuzzy logic to make better decisions by accounting for the inherent ambiguity in their risk assessments. This study looks at how the scenario method to risk assessment can be combined with fuzzy logic's mathematical foundation.